2009
DOI: 10.1111/j.1479-8425.2008.00381.x
|View full text |Cite
|
Sign up to set email alerts
|

How is autonomic nervous system activity in subjects who are sleepy but are unable to sleep in the daytime?

Abstract: We investigated changes in the activity of the autonomic nervous system (ANS) in the relaxed condition in subjects who felt sleepy, but were unable to sleep. A total of 1021 subjects underwent daytime polysomnography. The sleep latency (SL) and the visual analog scale (VAS) were used to assess "immediate" objective and subjective sleepiness, respectively. The subjects were assigned to an "Alert-Alert" group (VAS Յ 25 mm, SL Ն 8 min), a "Sleepy-Alert" group (VAS Ն 75 mm, SL Ն 8 min), or a "Sleepy-Sleepy" group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2011
2011
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
1
2
1
Order By: Relevance
“…In that same study, the sleepy and alert groups had CVI scores of 4.21 and 3.99, respectively, and CSI scores of 1.98 and 3.01, respectively. 42 In the present study, the CVI score prior to the regularized sleep-wake schedule was higher than the CVI score in the sleepy group in the previous study. However, this higher CVI score was decreased toward the lower level seen in the alert group when the habitual irregular sleep-wake schedule was regularized.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…In that same study, the sleepy and alert groups had CVI scores of 4.21 and 3.99, respectively, and CSI scores of 1.98 and 3.01, respectively. 42 In the present study, the CVI score prior to the regularized sleep-wake schedule was higher than the CVI score in the sleepy group in the previous study. However, this higher CVI score was decreased toward the lower level seen in the alert group when the habitual irregular sleep-wake schedule was regularized.…”
Section: Discussioncontrasting
confidence: 67%
“…In a previous study, daytime autonomic functions were measured in both a “sleepy” group, who showed greater than 75 mm in the VAS scale for sleepiness and less than 4 min in the sleep latency test during daytime, and an “alert” group, who showed less than 25 mm in the VAS for sleepiness and longer than 8 min in the sleep latency test during daytime. In that same study, the sleepy and alert groups had CVI scores of 4.21 and 3.99, respectively, and CSI scores of 1.98 and 3.01, respectively 42 . In the present study, the CVI score prior to the regularized sleep–wake schedule was higher than the CVI score in the sleepy group in the previous study.…”
Section: Discussionsupporting
confidence: 52%
“…Pivik and Busby (1996) found a decrease in heart rate 30 s before sleep stage 1. Furthermore, Morishima et al (2009) point to the role of the autonomic nervous system in difficulties with falling asleep during daytime. Our study is in line with these findings, as it shows that an increased level of autonomic activity induced by a stressful task interferes with falling asleep during daytime.…”
Section: Tablementioning
confidence: 98%
“…However, problems with falling asleep and maintaining daytime sleep in shift workers could partly be the consequence of psychosocial stress, which could interfere with sleep through somatic and cognitive arousal. A recent study by Morishima et al (118) explored the role of autonomic activity in subjects who felt sleepy but could not fall asleep in relaxed conditions during daytime. They found that problems with sleeping during the daytime happened to persons whose autonomic nervous activity did not show the expected decrease in the sympathetic and increase in parasympathetic activity in conditions which were convenient for relaxation and sleeping.…”
Section: Practical Implicatonsmentioning
confidence: 99%